PENGARUH KEPEMIMPINAN TRANSFORMASIONAL, MOTIVASI, PELATIHAN KERJA DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN PADA PERUSAHAAN DAERAH AIR MINUM (PDAM) TIRTA SATRIA KABUPATEN BANYUMAS - Nafis Mahesa Putra; Akhmad Darmawan; Suyoto Suyoto; Totok Haryanto (Jurnal Akuntansi dan Pajak, 2024)
This research aims to determine the influence of transformational leadership, motivation, training and work environment on employee performance at Perumdam Tirta Satria, Banyumas Regency. The population in this study was all employees at Perumdam Tirta Satria, Banyumas Regency, totaling 133 employees. The sampling technique uses purposive sampling with criteria namely general, financial and mechanical division employees, who have worked for more than one year, excluding leaders. The sample size in this study was 100 samples using the Slovin formula. Analysis uses multiple linear regression and correlation using SPSS version 26. The results of the research show that transformational leadership and motivation have a positive and significant effect on employee performance, training has an insignificant positive effect, while the work environment does not have a significant effect on employee performance. Keyword: transformational leadership, motivation, job training, work environment, and employee perfomance